Neonatal Fever in the COVID-19 Pandemic: Odds of a Serious Bacterial Infection. Issue 1 (23rd January 2022) - Mittal, Shraddha; Muthusami, Sunil; Marlowe, Lauren; Knerr, Sheila; Prasto, Julianne; Cooke, Tiffany Anise; Bochenski, Jacek; Horst, Michael A.
Abstract : Objectives: A sepsis workup is recommended in young infants 56 days or younger with fever to rule out a serious bacterial infection (SBI). Given the reduction in non–severe acute respiratory syndrome - coronavirus 2 viral infections observed in multiple studies during the coronavirus diseases 2019 (COVID-19) pandemic, we sought to determine if the reduction in viral infections led to a change in the incidence of SBI in this vulnerable patient population. Methods: We performed a multicenter, retrospective study of infants 56 days or younger presenting with fever to emergency departments of 6 community hospitals. We compared the incidence of SBIs, viral meningitis, and viral bronchiolitis during March 2020 to February 2021 (pandemic year) with the same calendar months in the 2 preceding years (prepandemic years). Results: From March 2018 to February 2021, 543 febrile infants presented to the emergency departments, 95 during the pandemic year (March 2020 to February 2021) compared with 231 and 217 in the prepandemic years (March 2018 to February 2019 and March 2019 to February 2020, respectively). During the pandemic year, 28.4% of infants (27 of 95) were diagnosed with an SBI compared with 11.7% and 6.9% ( P < 0.001) in the prepandemic years (27 of 231 and 15 of 217, respectively). Five patients were diagnosed with bacterial meningitis over the 3-year period, 4 of them during the pandemic year (4 of 95 [4.2%]). Positivity for viral cerebrospinal fluid polymerase chain reaction during the pandemic year was 6.4% (3 of 47) compared with 20.8% (25 of 120) and 20.4% (23 of 113) in prepandemic years ( P = 0.070). During the pandemic year, 2.1% (2 of 95) febrile young infants were admitted with a comorbid diagnosis of bronchiolitis compared with 4.3% and 6.0% in the prepandemic years ( P = 0.310). Conclusions: The COVID-19 pandemic led to an increase in the incidence of SBIs in febrile infants 56 days or younger, likely a result of reduction in non–severe acute respiratory syndrome - coronavirus 2 viral infections. Greater vigilance is thus warranted in the evaluation of febrile infants during the COVID-19 pandemic.